On the identities of Caecilia degenerata Dunn, 1942 and of C. corpulenta Taylor, 1968 (Amphibia: Gymnophiona: Caeciliidae) with descriptions of three new species of Caecilia Linnaeus, 1758 from the Cordillera Oriental of Colombia - Fernández-Roldán, Juan David; Lynch, John D.; Medina-Rangel, Guido Fabian (Zootaxa, 2023)
The Central portion of the Cordillera Oriental of Colombia is currently reported to harbor two species of Caecilia distributed at comparable elevations on opposite versants of these Mountains. These are C. corpulenta, known from Virolín, Santander, at 1700–2000 m on the western slopes of the Cordillera Oriental and C. degenerata, known from Garagoa, Boyacá, and Choachí and Fomequé, Cundinamarca, at 1800–2100 m on the eastern slopes of the Cordillera Oriental. Both species have dermal scales and lack secondary grooves, and have been subjected to misidentifications by herpetologists studying the Gymnophiona of the Eastern Andes of Colombia. Our results indicate that only the latter species is found in Colombia and the former is restricted to Peru, leaving those populations previously referred to C. corpulenta and those distinct from C. degenerata pending names. We here present an account for C. degenerata based on material from Choachí and Fómeque, Cundinamarca, as well as descriptions of three new species from the Cordillera Oriental and adjacent Venezuela: C. atelolepis sp. nov., C. epicrionopsoides sp. nov., and C. macrodonta sp. nov. We also provide additional morphological information for the recently described C. pulchraserrana.